Knockdown of TRIM65 Inhibits Neoangiogenesis in Proliferative Diabetic Retinopathy by Regulating miR29a-3p - Chen, Xinxin; Chen, Xiaolong; Huang, Shuai; Xian, Yang; Han, Ruining (Current Medicinal Chemistry, 2025)
IntroductionHigh glucose-induced angiogenesis is the main component in Proliferative Diabetic Retinopathy (PDR) development. In PDR, ischemia and hypoxia have been identified as key stimuli that promote pathological neoangiogenesis by increasing Vascular Endothelial Growth Factor A (VEGFA). Furthermore, it has been demonstrated that TRIM65 knockdown in tumor cells reduces VEGFA expression. Building on these findings, the present study aimed to study the role of TRIM protein members in proliferative diabetic retinopathy.MethodsIn comparison to the control group, TRIM65 expression was significantly increased in human retinal endothelial cells (HREC) after high glucose treatment. Moreover, FITC/PI staining, cell wound scratch assay, transwell assay, tube formation assay, and immunofluorescence staining of VEGFA and HIF-3α were carried out, which indicated that TRIM65 knockdown inhibited high glucose-induced HREC cell apoptosis and angiogenesis and decreased the expression of VEGFA and HIF-3α, both of which are potential targets of miR-29a-3p. MIR-29a-3p inhibitor significantly reduced the effects of TRIM65 knockdown on VEGFA and HIF-3α expression levels in cells. TRIM65 induced ubiquitination and degradation of TNRC6A, resulting in suppressed miR-29a-3p expression.ResultsFurthermore, in vivo studies revealed that intravitreal injection of miR-29a-3p inhibited neoangiogenesis in mice with Oxygen-Induced Retinopathy (OIR). The retinal tissues of OIR mice showed higher TRIM65 mRNA expression and lower miR-29a-3p expression than those of control mice. Furthermore, the analysis showed a negative correlation between the expression of miR-29a-3p and TRIM65 in the retinal tissues of OIR mice.ConclusionIn conclusion, this study demonstrated that the knockdown of TRIM65 inhibits neoangiogenesis in proliferative diabetic retinopathy by regulating miR-29a-3p.
Keywords: retinal endothelial cells